Pengaruh E-Service Quality, Electronic Word of Mouth (E-Wom), dan Product Quality terhadap Consumer Repurchase Intention: Studi pada Pelanggan Fore Coffee di Denpasar - Ni Kadek Ayu Diah Monica Sari; Ni Made Wulandari Kusumadewi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of e-service quality, electronic word of mouth (e-WOM), and product quality on consumer repurchase intention among Fore Coffee customers in Denpasar. The background of this research is driven by the rapid growth of the coffee shop industry in Indonesia, accompanied by the increasing use of digital technology in service delivery and marketing, highlighting the importance of understanding factors that influence customer loyalty. This study employs a quantitative approach with an associative method, involving 105 respondents selected through purposive sampling, and analyzed using multiple linear regression. The results show that e-service quality, electronic word of mouth (e-WOM), and product quality have a positive and significant effect on repurchase intention, both partially and simultaneously. Among the variables, e-WOM has the most dominant influence, followed by product quality and e-service quality. These findings indicate that high-quality digital service experiences, positive online reviews, and consistent product quality contribute to building customer trust, satisfaction, and loyalty. Additionally, the model explains 45.6% of the variance in repurchase intention, suggesting that these three variables play a substantial role in influencing repeat purchase behavior. The implications of this study emphasize that improving application-based service quality, managing e-WOM strategically, and maintaining consistent product quality are key factors in strengthening competitiveness and customer loyalty in the digital-based coffee shop industry. This research is expected to provide practical insights for companies in designing customer experience-oriented marketing strategies and serve as a reference for future studies in similar contexts.